1993
DOI: 10.1002/ijc.2910550505
|View full text |Cite
|
Sign up to set email alerts
|

Specific expression of the pancreatic‐secretory‐trypsin‐inhibitor (PSTI) gene in hepatocellular carcinoma

Abstract: Twenty hepatocellular carcinomas (HCC) were analyzed by Northern blotting to test the expression of pancreatic secretory trypsin inhibitor (PSTI). This gene was expressed in all HCCs, but not in other tumors, including mammary, thyroid, pulmonary and ovarian cancers. Some gastric and colonic cancers weakly expressed PSTI. Among cell lines examined in a similar manner, PSTI was expressed in all of 4 derived from hepatoma. On the other hand, among 15 cell lines derived from cancers other than hepatoma, only 3, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 23 publications
1
44
0
Order By: Relevance
“…Furthermore, these results suggest that SPINK1 overexpression could be used as a diagnostic marker for HCC. The plasma concentrations of SPINK1 are significantly increased in HCC patients and the concentrations correlated with tumor size (37 ). Recently, serum SPINK1 has been found to be a strong prognostic factor in HCC (41 ).…”
Section: Hepatocellular Cancermentioning
confidence: 99%
“…Furthermore, these results suggest that SPINK1 overexpression could be used as a diagnostic marker for HCC. The plasma concentrations of SPINK1 are significantly increased in HCC patients and the concentrations correlated with tumor size (37 ). Recently, serum SPINK1 has been found to be a strong prognostic factor in HCC (41 ).…”
Section: Hepatocellular Cancermentioning
confidence: 99%
“…SPINK1 is also produced in cancers of the colon (15,16), lung (17,18), liver (19), breast (20), prostate (21), and pancreas (20,22). In colon cancer, Gouyer and colleagues (23) identified and characterized SPINK1 as a major proinvasive secreted factor from the conditioned medium of HT-29 5M21 human colon cancer cells, which express a spontaneous invasive phenotype.…”
Section: Introductionmentioning
confidence: 99%
“…Its role has been considered to be a specific inhibitor that prevents autoactivation of trypsinogen in the pancreas and pancreatic juice [41]. Later studies showed that PSTI was also expressed in some extrapancreatic normal tissues [39,4345] and in various cancers, including pancreatic [34], colorectal [35], gastric [36], lung [37], and hepatocellular [38] cancers. It was found that the serum concentration of immunoreactive PSTI is elevated after surgery, trauma and severe infection [45][46][47], suggesting that PSTI is an acute phase reactant.…”
Section: Controlmentioning
confidence: 99%
“…2 and 3), although the liver specimens of most type I1 patients tested in the present paper did not show any histological appearance as cancer. It was suggested that the PSTI gene is regulated by the AP-I binding site and IL-6 responsive element, and each region is active in hepatoma cells [38]. However, the biological implication of the high PSTI gene expression in hepatic cancer is not yet understood.…”
Section: Controlmentioning
confidence: 99%